(untitled) (Revista Cocar, 2019)
The use of the participle in verbal formations in the portuguese of Baixo Tocantins Resumo Este artigo investiga o uso do particípio na construção de tempo composto e voz passiva do português falado no Baixo Tocantins. Nele, objetivamos verificar a forma mais preponderante de particípio em formações verbais; a interferência de fatores linguísticos e extralinguísticos na opção do falante pela forma regular ou irregular do particípio; contrapor a norma gramatical com o uso do particípio em situações reais de fala. O corpus desta pesquisa é constituído de dados de duas naturezas, a primeira proveniente de entrevistas para caracterizar o uso do particípio na fala espontânea e a outra de testes de produtividade, por que desejávamos levantar o uso específico do particípio irregular. Ambos os métodos foram aplicados com 8 colaboradores de diferentes escolaridades, moradores da zona urbana e rural da região do baixo Tocantins. Nos resultados preliminares dos testes com os verbos e as formações verbais utilizadas, o uso do particípio mostrou-se predominantemente alternante, ou seja, os falantes alternam as formas regulares e irregulares de particípio em formação com voz passiva e tempo composto. Palavras-chave: Verbos regulares e irregulares. Particípios. Norma e uso. Alternância; Abstract The current work deals the use of the participle in the construction of the compund tense and the passive voice of the spoken Portuguese language, in the Baixo Tocantins. Specifically we objective to observe the most preponderant form of the participle in the verbal constructions; the interference of the extralinguistic and linguistic factors in the optional choice of speaker by the irregular and regular form of the participle and to oppose the grammatical rules with the use of the participle in the real situations of speech. The corpus is the constitutive of data of two natures: the first, obtained through interviews, to characterize the use of participle in the spontaneous speech, and the second, abtained through of the productivity tests, because we wish to make the survey of the especific use of irregular participle. Both methodologies were apply in eight groups of students of different schoolings, residentes from rural and urban área in the municipality of Baixo Tocantins. In the preliminary results of the tests with verbs and the verbs and the used verbal formations, the use participle showed predominantly alternating, that is, the speakers alternant the irregular and irregular forms of the participle in formation with passive voice and compound tense. Keywords: Irregular and regular verbs. Participles. Grammatical Rules use. Alternation